Analisis Penerapan PSAK 109 pada Baznaz Kota Medan Tahun 2020-2021 - Fitri Rahmayani; Juliana Nasution (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
BAZNAZ Medan is one of the official bodies established by the government which is trusted by the government to collect, manage and distribute zakat, alms infaq to mustahik in the city of Medan. This study aims to analyze the application of PSAK 109 in the presentation of BAZNAS financial statements in the city of Medan. The research method used is a qualitative research method with a descriptive method. The data used in this study are primary data and secondary data, with data collection techniques in the form of triangulation techniques. The data analysis method used is data reduction, data presentation, final verification/conclusion. The results of this analysis show that Medan City BAZNAZ in presenting the main points has implemented PSAK 109. Although Medan City BAZNAZ has implemented ZIS calculations, most of BAZNAZ's final obligations have not fully complied with PSAK. This study aims to determine the application of PSAK 109 at the Amil Zakat Agency of MEDAN City. This type of research is a type of qualitative research. Data collection methods used are direct observation, interviews, and documentation. The results of this study can be concluded that the accounting management at the Medan City Amil Zakat Agency has not fully implemented PSAK 109